The discovery of a type-II quasar at z = 1.65 with integral-field spectroscopy - Jarvis, M; Breukelen, C; Wilman, R (2004)
In this letter we report the serendipitous discovery of a genuine type-II quasar at z = 1.65 using integral-field data from VIMOS on the VLT. This is the first discovery of a type-II quasar at z > 1 from optical data alone. J094531-242831, hereafter J0945-2428, exhibits strong narrow (v < 1500km/s) emission lines, has a resolved host galaxy, and is undetected to a radio flux-density limit of S_{5GHz} = 0.15 mJy (3 sigma). All of these lead us to believe that J0945-2428 is a bona fide type-II quasar. The luminosity of the narrow-emission lines in this object suggest that the intrinsic power of the central engine is similar to that found in powerful radio galaxies, indicative of similarly large supermassive black hole of ~3 x 10^8 M_solar (assuming that it is accreting at its Eddington limit). However, from near-infrared imaging observations we find that the old stellar population in the host galaxy has a luminosity of ~0.2 L*, mildly inconsistent with the correlation between black-hole mass and bulge luminosity found locally, although the uncertainty in the black-hole mass estimate is large. This discovery highlights the power that integral-field units have in discovering hidden populations of objects, particularly the sought after type-II quasars which are invoked to explain the hard X-ray background. As such, future large integral-field surveys could open up a new window on the obscured accretion activity in the Universe.